Międzynarodowe aspekty reform Wspólnej Polityki Rolnej Unii Europejskiej - SKRZYPCZYŃSKA, JOANNA (Wydawnictwo Naukowe UAM, 2011)
The aim of these considerations was to present the effect of regulations implemented by the World Trade Organisation on the form of agricultural policy in the European Union. The first part of this paper introduces the subject of agriculture in GATT and the WTO as well as changes in the agricultural policy of the EC connected with negotiations held at that time. The second part of the paper concerns negotiations on agriculture conducted within the Development Round of the WTO as well as potential changes to the EU agricultural policy after 2013. The Common Agricultural Policy occupies a special position in the European Union. Its role is not limited to the protection of the EU market against foreign competition, but also serves many functions connected with food safety, sustainable development, regional cohesion and other common goals of the EU. Further liberalisation of CAP requires from the European Commission the support for this idea by the member countries. The future agricultural policy of the EU has to combine many contradictory goals, in-cluding the prevention of a reduction in agricultural revenue, protection of the European model of agriculture as well as assurance of competitiveness for European agricultural produce on the world market, at the simultaneous maintenance of obligations resulting from negotiations conducted with the WTO.

Lo scopo delle considerazioni è di mostrare l’impatto delle regole dell’Organizzazione Mondiale del Commercio sull’assetto della politica agricola dell’Unione Europea. La prima parte dell’articolo costituisce un'introduzione alla problematica agricola sul forum del GATT e della WTO ed a quella dei cambiamenti nella politica agricola della CE legati alle trattative allora in corso. La seconda parte riguarda i negoziati agricoli svolti nell’ambito del Development Round della WTO e i potenziali cambiamenti nella politica agricola dell’UE dopo il 2013. La Politica Agricola Comune occupa una posizione unica all’interno dell’Unione Eu-ropea. Il suo ruolo non si limita solo a proteggere il mercato dell’UE dalla concorrenza straniera, ma svolge anche molte funzioni relative al problema di sicurezza alimentare, sviluppo sostenibile, coesione territoriale e ad altri obiettivi comuni dell’UE. L’ulteriore liberalizzazione della PAC richiede che la Commissione ottenga il sostegno degli Stati membri a questa idea. La futura politica agricola dell’UE deve conciliare diversi obiettivi in conflitto, tra cui contrastare il calo dei redditi agricoli, tutelare il modello agricolo europeo, ed anche garantire la competitività dei prodotti agricoli europei nel mercato globale, pur mantenendo gli obblighi derivanti dalle trattative svolte nell’ambito della WTO.